Omics strategies for crop improvement in response to climate change‐imposed abiotic stress - Shourie, Abhilasha; Madaan, Nishtha; Saini, Paridhi (Indonesian Journal of Biotechnology, 2024)
Given the current status of climate change and its impact on global food security, it is imperative to improve the abiotic stress tolerance of crop plants to enhance productivity. Traditional plant breeding methods have been widely employed to develop climate‐resilient crops; however, their success has been limited due to the lack of understanding of the complex relationships between genes and stress‐related phenotypes. The advent of modern genomics has enabled the expression analysis of stress genes in plants, as genome‐wide information is readily accessible and can be utilized to assign and validate the gene functions. This article highlights the potential applications and limitations of present‐day genomic technologies based on genome mapping, gain or loss‐of‐function analysis for identification of the role of a particular gene in abiotic stress response in plants. Such technologies are highly efficient in candidate gene identification; gene‐trait relationships establishment; functional elucidation of genes; and stress genes modification in crop plants. Modern high throughput genomic technologies offer wide scope for deciphering the complexities of genetic regulation of stress in plants; modulating stress responses; and developing stress tolerance in crop plants against drought, temperature, salinity, osmotic imbalance, herbicides and heavy metal toxicity.